Moderating role of religiosity on Zakat compliance behavior in Nigeria - Farouk, Abubakar U.; Md Idris, Kamil; Saad, Ram Al Jaffri (Emerald Publishing Limited, 2018)
Purpose: This paper examines the moderating effect of religiosity in the theory of reasoned action (TRA) on intention to comply with the Zakat on employment income (ZEI).Design/methodology/approach: A survey of civil servants in Kano State, Nigeria was carried out and 474 valid observations were retrieved from the 700 distributed questionnaires. Partial least squares structural equation modeling (PLS-SEM) was used to validate the instrument that measures the variables, examined the structural model and the predictive relevance of the study's model.Findings: The results revealed the suitability of both the TRA and the PLS-SEM in the study of ZEI behavioral intention in a developing country. All the hypothesized direct relationships were supported on the one hand. On the other hand, one of the two indirect relationships, subjective norm and behavioral intention moderated by religiosity was supported, but the other tests for moderating effects of religiosity on the relationship between attitude and behavioral intention was not.Practical implications: Public and private Zakat institutions in Muslim majority societies in Nigeria and in other Muslim countries may use the findings to focus their attention on the formulation of policies based on the findings of the study to strengthen eligible Zakat payers’ intention to comply to further boost their Zakat collections.Originality/value: This study extends the TRA in the context of ZEI by proposing religiosity as a moderator in the predictive capacity of TRA on ZEI. Moreover, the suitability for the use of PLS-SEM as a statistical tool in investigating the extended TRA with religiosity as a moderating variable as well as its implications for theory and practice were also discussed.